Green synthesis and characterization of Dy2Ce2O7 nanostructures using Ananas comosus with high visible-light photocatalytic activity of organic contaminants - Zinatloo-Ajabshir, Sahar; Salehi, Zahra; Salavati-Niasari, Masoud (Journal of alloys and compounds, 2018)
An easy and eco-friendly viable way has been utilized to synthesize nano-scale Dy2Ce2O7 with employing extract of Ananas comosus as new and efficient bio fuel, for the first time. The amount of extract of Ananas comosus has been altered to explore its impact on shape, catalytic yield and dimension of Dy2Ce2O7. The purity, optical features and shape of the resulting Dy2Ce2O7 have been determined with FESEM, EDS, XRD, DRS and TEM. Further, the catalytic yield of various samples of dysprosium cerate has been examined for eriochrome black T degradation under visible illumination. The nano-scale Dy2Ce2O7 synthesized with employing appropriate amount of extract of Ananas comosus as new and efficient bio fuel, exhibited superior photocatalytic yield in the contaminant destruction. [Display omitted] •An easy and eco-friendly viable way was utilized to synthesize nano-scale Dy2Ce2O7.•Extract of Ananas comosus as new and efficient bio fuel was employed.•The Ananas was altered to explore its impact on shape, catalytic yield and dimension of Dy2Ce2O7.•The catalytic yield of various samples was examined for dye T degradation under visible illumination.•The nano-scale Dy2Ce2O7 exhibited superior photocatalytic yield in the contaminant destruction.